2018
DOI: 10.1186/s12888-018-1676-0
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric properties of the Arabic version of the confusion assessment method for the intensive care unit (CAM-ICU)

Abstract: BackgroundIt is recommended that critically ill patients undergo routine delirium monitoring with a valid and reliable tool such as the Confusion Assessment Method for the Intensive Care Unit (CAM-ICU). However, the validity and reliability of the Arabic version of the CAM-ICU has not been investigated. Here, we test the validity and reliability of the Arabic CAM-ICU.MethodsWe conducted a psychometric study at ICUs in a tertiary-care hospital in Saudi Arabia. We recruited consecutive adult Arabic-speaking pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…The CAM-ICU is a valid and reliable delirium assessment tool. Patients with a RASS score of − 3 or lower will be excluded from CAM-ICU assessment, as they cannot participate in the exam [26]. We will calculate the modified Clinical Pulmonary Infection Score (CPIS) to differentiate secretions caused by patients' underlying lung pathology (ventilator-associated pneumonia [VAP]) vs ketamine-associated hypersalivation [27].…”
Section: Data Managementmentioning
confidence: 99%
“…The CAM-ICU is a valid and reliable delirium assessment tool. Patients with a RASS score of − 3 or lower will be excluded from CAM-ICU assessment, as they cannot participate in the exam [26]. We will calculate the modified Clinical Pulmonary Infection Score (CPIS) to differentiate secretions caused by patients' underlying lung pathology (ventilator-associated pneumonia [VAP]) vs ketamine-associated hypersalivation [27].…”
Section: Data Managementmentioning
confidence: 99%
“…Table S3 presents the characteristics of the 29 studies. Twenty-three and 8 studies reported accuracy estimates for CAM-ICU (Adamis et al, 2012;Aljuaid et al, 2018;Barman et al, 2018;Boettger et al, 2018;Chanques et al, 2018;Chuang et al, 2007;Ely, Margolin, et al, 2001;Guenther et al, 2010;Gusmao-Flores et al, 2011;Heo et al, 2011;Karlicic et al, 2016;Koga et al, 2015;Lin et al, 2004;Luetz et al, 2010;Mitášová et al, 2012;Nishimura et al, 2016;Pipanmekaporn et al, 2014;Selim et al, 2018;van Eijk et al, 2011;van Eijk et al, 2009;Vreeswijk et al, 2009;Wang et al, 2013) and ICDSC (Barman et al, 2018;Bergeron et al, 2001;Boettger et al, 2018;Chanques et al, 2018;Gusmao-Flores et al, 2011;Kose, Bolu, Ozdemir, Acikel, & Hatipolu, 2016;Nishimura et al, 2016;van Eijk et al, 2009), respectively. Two studies applied Delirium Detection Score (DDS) (Luetz et al, 2010;Otter et al, 2005), one applied Cognitive Test for Delirium (CTD) alone (Hart et al, 1996), one applied Stanford Proxy Test for Delirium (S-PTD) alone (Alosaimi et al, 2018), one applied Neelon and Champagne Confusion Scale (NEECHAM) alone (Immers, Schuurmans, & Van De Bijl, 2005), and one applied Nursing Delirium Screening Scale (Nu-DESC) for delirium assessmen...…”
Section: Resultsmentioning
confidence: 99%
“…First, although back-translation combined with both monolingual and bilingual tests is the most complete instrument for the translation procedure [25], the above method could not be used in this study because there were not enough bilingual subjects. Secondly, as in previous validation studies [11,14,28,29,31], patients with dementia and neuropsychiatric diseases were excluded. Further studies are needed to assess the psychometric properties of CAM-ICU in those patients.…”
Section: Validity: Internal Consistency Sensitivity and Specificitymentioning
confidence: 99%